2005
DOI: 10.1016/s1808-8694(15)31248-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with benign paroxysmal positional vertigo and/or Ménière's disease

Abstract: Ménière's disease patients presented worse quality of life when compared to BPPV patients, in and out of crisis, and during the crisis when regarding the patients with association of both disorders. The damage on quality of life was independent of gender, age and in the BPPV cases it was independent of posterior canal affection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 9 publications
2
13
0
1
Order By: Relevance
“…The postural instability complaint was present in most of the cases (84.0%); in agreement with the statement that vestibular disorder symptoms in BPPV patients include not only the vertigo and unbalance fits caused by a sudden change in head position, but there is also an increase in postural sway during the vertigo episodes 4 . The Brazilian version 17 of the Dizziness Handicap Inventory 16 used indicated a moderate influence (mean of 49.11 points) of symptoms in quality of life 23 , similarly to what was previously found (mean of 52.89 points) in BPPV patients before treatment 6 . The mean value of 7.24 points upon the dizziness analog scale 18 suggested severe dizziness in the series evaluated.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The postural instability complaint was present in most of the cases (84.0%); in agreement with the statement that vestibular disorder symptoms in BPPV patients include not only the vertigo and unbalance fits caused by a sudden change in head position, but there is also an increase in postural sway during the vertigo episodes 4 . The Brazilian version 17 of the Dizziness Handicap Inventory 16 used indicated a moderate influence (mean of 49.11 points) of symptoms in quality of life 23 , similarly to what was previously found (mean of 52.89 points) in BPPV patients before treatment 6 . The mean value of 7.24 points upon the dizziness analog scale 18 suggested severe dizziness in the series evaluated.…”
Section: Discussionsupporting
confidence: 79%
“…Although BPPV patients primarily have short--duration vertigo fits, postural instability and loss of body balance may also happen in-between fits 3,4 , or after particle repositioning maneuvers 5 . In those cases of persistent vertigo, the disorder may become incapacitating and impair daily life activities; life-quality loss is greater during the fits; although it may also happen outside of the fits; physical aspects are the most altered, followed by the functional and emotional ones 6 . BPPV is the most common cause of vertigo among adults, representing about 20% of causes of dizziness 7 .…”
Section: Introductionmentioning
confidence: 99%
“…26 Several studies have used the Brazilian DHI as a suitable tool to assess the limiting effects of dizziness; furthermore, this tool is easy to use, and easy for the patients to understand. 28 35 In this study, results showed subjects with normal and high examination scores on the DHI, demonstrating that, for some patients with normal test results, dizziness has a higher impact on the patient's quality of life. However, there were individuals with modified results in the national criterion (UW and/or DP greater than 33%) with low scores on the Brazilian DHI.…”
Section: Discussionmentioning
confidence: 65%
“…However, studies show that the diseases that lead to transient dizziness present higher commitment of the physical aspects evaluated by the DHI. Nevertheless, emotional aspects occur as a consequence of the long lasting physical limitations and functional incapacily due to dizziness 28 . Psychological fators are largely known as triggers for dizziness and therefore may be associated to a low score in quality of life scales 29 .…”
Section: Discussionmentioning
confidence: 99%